Theory and design of thermoelectric generators using waste heat on vehicles - Kuz, R.V. (Journal of Thermoelectricity, 2020)
The paper presents the results of the analysis of theoretical works concerning the use of thermoelectric generators for vehicles in order to obtain additional electricity and, accordingly, fuel saving. The trends and current state of development of such generators are considered. Bibl. 21.